Evolução do reparo por excisão de nucleotídeo - Silva, Uaska Bezerra e (2008)
The phylogeny is one of the main activities of the modern taxonomists and a way to reconstruct the history of the life through comparative analysis of these sequences stored in their genomes aimed find any justification for the origin or evolution of them. Among the sequences with a high level of conservation are the genes of repair because it is important for the conservation and maintenance of genetic stability. Hence, variations in repair genes, as the genes of the nucleotide excision repair (NER), may indicate a possible gene transfer between species. This study aimed to examine the evolutionary history of the components of the NER. For this, sequences of UVRA, UVRB, UVRC and XPB were obtained from GenBank by Blast-p, considering 10-15 as cutoff to create a database. Phylogenetic studies were done using algorithms in PAUP programs, BAYES and PHYLIP package. Phylogenetic trees were build with protein sequences and with sequences of 16S ribosomal RNA for comparative analysis by the methods of parsimony, likelihood and Bayesian. The XPB tree shows that archaeal´s XPB helicases are similar to eukaryotic helicases. According to this data, we infer that the eukaryote nucleotide excision repair system had appeared in Archaea. At UVRA, UVRB and UVRC trees was found a monophyletic group formed by three species of epsilonproteobacterias class, three species of mollicutes class and archaeabacterias of Methanobacteria and Methanococci classes. This information is supported by a tree obtained with the proteins, UVRA, UVRB and UVRC concatenated. Thus, although there are arguments in the literature defending the horizontal transfer of the system uvrABC of bacteria to archaeabacterias, the analysis made in this study suggests that occurred a vertical transfer, from archaeabacteria, of both the NER genes: uvrABC and XPs. According the parsimony, this is the best way because of the occurrence of monophyletic groups, the time of divergence of classes and number of archaeabacterias species with uvrABC system